Nesidiocoris tenuis (Hemiptera: Miridae) predator in tobacco crops (Nicotiana tabacum) - VALDERRAMA, KATERINE; GRANOBLES, JAIME; VALENCIA, EDISON; SÁNCHEZ, MANUEL (Revista Colombiana de Entomología, 2007)
Pests of tobacco (Nicotiana tabacum) and their natural enemies crops were identified in the main cultivated areas of Colombia. Weekly sampling was carried out over two cycles of the crop. The hemipteran Miridae Nesidiocoris tenuis was observed to be a predator. The main prey are three of the major pests of tobacco crops: Trialeurodes vaporariorum, Bemisia tabaci and Myzus persicae. Tobacco is associated with populations of these pests from the nursery to the final harvest. Up to now N. tenuis has been considered by tobacco farmers to be an enemy of their crop and they make pesticide applications for its control. To obtain additional information on N. tenuis, its predatory habits in the field and its functional response in the laboratory on the prey T. vaporariorum y M. persicae were evaluated. Colonies of the predator and prey were established in cages at La Tupia field station (Candelaria, Valle). Nymphs of T. vaporariorum were placed in Petri dishes with one adult predator. Nymphs and adults of M. persicae were also put in Petri dishes with one adult predator. N. tenuis preferentially preys on first and second instar whiteflies while it prefers larger nymphs and adults of M. persicae. This research is a contribution toward the efficiency and competitiveness of this crop in cultivated areas of the country, due to the current pest problems in each area and the lack of knowledge on the biological agents associated with tobacco crops in Colombia.